Does the administration of antioxidants as scavengers of reactive oxygen species in kidney transplantation really have sense? - Kuntscher, Vilém; Třeška, Vladislav; Racek, Jaroslav; Kobr, Jiří; Trefil, Ladislav; Hes, Ondřej (Bratislavské lekárske listy, 2007)
BACKGROUND: The aim of the study was to evaluate the degree of ischemia reperfusion syndrome (IRS) in serious ischemic insult of a kidney transplant and to try to mitigate the production of reactive oxygen substances (ROS) and inflammatory response. METHODS: The study was performed on 14 white pigs (20 kg). The pigs were divided in couples using a negative cross-matching and the couples were divided into the two groups. Each animal from the compatible couple was a donor/recipient of a kidney to/from the counterpart. Group II (TxII) received the intravenous antioxidants. Group I (TxI) was a control group. L-ascorbic acid 125 mg, selenium 4.4 mg, tocoferol 50 mg and N-acetyl-cysteine 200 mg were used as the antioxidants. They were applied intravenously to the TxII animals for 20 minutes before reperfusion of a kidney transplant. A serious ischemic insult was created by the left kidney hilum's cross-clamping for 30 min before donation. After the kidneys' removal, the left ones were flushed with Histidine Tryptophan Ketoglutarate (HTK) preservation solution and transplanted after the 1.5 hour (in the meantime stored in melted ice). Venous blood samples were taken for the assessment of malondialdehyde (MDA), reduced glutathione (GSH), glutathioneperoxidase (GSHPx), antioxidative capacity of plasma (AOC), interleukin 6 (IL-6), and tumor-necrosis factor alfa (TNFalfa) prior to the nefrectomy, before application of ROS scavengers (TxII), and during the 120-minute period after the transplantation (TxL+TxII). RESULTS: There wasn't a significant difference neither in production of MDA, nor in the levels of GSH, GSHPx, AOC, IL6 and TNFalfa between the TxI and TxII groups. CONCLUSIONS: Based on our results, we cannot conclude that the intravenous application of ROS scavengers in given combination and amount, administered to the recipient in the period just before transplantation, is a useful protective mechanism against kidney damage during IRS (Fig. 3, Ref. 17). Full Text (Free, PDF) www.bmj.sk.
Keywords: transplantace ledvin; reaktivní formy kyslíku; financování organizované; Animals; Reperfusion Injury; Financing, Organized; Free Radical Scavengers; reperfuzní poškození; Antioxidants; zvířata; Kidney Transplantation; scavengery volných radikálů; intravenózní infuze; Reactive Oxygen Species; Infusions, Intravenous; antioxidancia; Sus scrofa